2020
DOI: 10.1016/j.wneu.2020.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Among Neurosurgeons and Residents in Neurosurgery: A Systematic Review and Meta-Analysis of the Literature

Abstract: Background Burnout syndrome (BS) is a common condition among medical professionals. It is composed of 3 different subdimensions: emotional exhaustion (EE), depersonalization (DP), and reduced personal accomplishment (PA). In the last years, interest in BS in the neurosurgical community has increased. Here we investigated burnout among neurosurgeons and residents in neurosurgery. Methods A systematic review with meta-analysis was performed following PRISMA guidelines. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 35 publications
2
40
0
1
Order By: Relevance
“…The results of this study highlight the beneficial role of social support as a mediator between the negative effects of burnout on general health among health care professionals in Ecuador, which was unexplored prior to this study. These results are consistent with previous studies, which reported high rates of burnout among health care professionals in other countries (Li et al, 2018;Korkmaz et al, 2020;Zaed et al, 2020;Zaghini et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study highlight the beneficial role of social support as a mediator between the negative effects of burnout on general health among health care professionals in Ecuador, which was unexplored prior to this study. These results are consistent with previous studies, which reported high rates of burnout among health care professionals in other countries (Li et al, 2018;Korkmaz et al, 2020;Zaed et al, 2020;Zaghini et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…The pandemic situation affects students' well-being, as the results of a negative PCI (including concerns about academic future and completing the semester) show. Considering a strong relationship between perceived stress, mental health, and problems with academic life with burnout syndrome [79][80][81][82], we want to shed light on possible outcomes of high stress levels that could lead to academic burnout in the future.…”
Section: Exploring Perceivedmentioning
confidence: 99%
“…In contrast to previous studies based in the USA and China [ 29 ], the participants in this study all work in a public health system, the National Health Service (NHS), rather than private- or insurance-based systems. Furthermore, other studies used the MBI questionnaires; therefore, whilst it is not possible to directly compare the burnout scores in our study to those previous studies, it is interesting that similar factors have been found to be associated with higher levels of burnout.…”
Section: Discussionmentioning
confidence: 99%
“…Included in this have been a small handful of studies looking into the presence of burnout amongst neurosurgeons. A systematic review of these found the prevalence of burnout in neurosurgeons to be just under 50% [ 29 ]. Previous studies have shown that burnout is associated with negative individual psychological consequences and, on a systems-level, leads to increased medical errors and potential compromise of patient safety [ 21 ].…”
Section: Introductionmentioning
confidence: 99%